WATER RESOURCES MANAGEMENT TO FULFILL THE BASIC NEEDS OF THE COMMUNITY - Indrati Rini (International Journal of Social Science, 2022)
Water resources are the basic needs of society that must be met by the State. The fulfillment of water resources carried out by the central government and local governments have not been fulfilled optimally. The problem is why the state is given the authority to manage water resources, how does the government fulfill water resources as the basic needs of the community, and whether the water resources in the community have been met. The normative legal research method is used in analyzing secondary data. The government has made efforts to manage the need for water resources, but it has not been fulfilled in its entirety, so strategic steps are needed to overcome it.